2008
DOI: 10.1007/s00520-008-0512-3
|View full text |Cite
|
Sign up to set email alerts
|

Associations between quality of life, fatigue, and cytokine levels in patients aged 50+ with acute myeloid leukemia

Abstract: These preliminary data provide support for a larger controlled study of cytokines, fatigue, and QOL in patients with AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 39 publications
0
20
0
2
Order By: Relevance
“…Decreased expression of IL-5, an important regulator of microglia and infiltrating macrophages in the brain [69], was also identified in tumor-bearing mice and tumor-free mice receiving radiotherapy alone. Associations with IL-5 and cancer-related fatigue have previously been described clinically [70]. Tumor-free mice receiving only radiotherapy also demonstrated decreased cortical expression of IL-6, which has been widely recognized as one of the most important regulators of neuroimmune function and has been repeatedly associated with cancer-related neurological dysfunction [15, 7173].…”
Section: Discussionmentioning
confidence: 93%
“…Decreased expression of IL-5, an important regulator of microglia and infiltrating macrophages in the brain [69], was also identified in tumor-bearing mice and tumor-free mice receiving radiotherapy alone. Associations with IL-5 and cancer-related fatigue have previously been described clinically [70]. Tumor-free mice receiving only radiotherapy also demonstrated decreased cortical expression of IL-6, which has been widely recognized as one of the most important regulators of neuroimmune function and has been repeatedly associated with cancer-related neurological dysfunction [15, 7173].…”
Section: Discussionmentioning
confidence: 93%
“…Seven of these studies showed significant associations between fatigue and an immunogenomic marker. Eleven different fatigue measures were used in the 10 longitudinal studies, with one study using multiple fatigue scales (Panju et al, 2009) and another using an interview to measure fatigue (Olson et al, 2002). Three of these fatigue questionnaires were administered and validated in non-English languages (Ahlberg et al, 2004; Geinitz et al, 2001; Reinertsen et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Increased production of cytokines such as TNFa, IL-6 and IL-10 by leukemic blasts and immune system cells has been reported in AML patients, but their role in pathogenesis of these patients is still not well understood [79]. IL-6 leads to activation of STAT3/5 transcription factors followed by increased expression of Twist1/2 proteins, because STAT3/5 is an upstream activator of Twist (Fig.…”
Section: Expression and Alternation Of Twist In Hematological Malignamentioning
confidence: 97%